Design and development of mopping robot-‘HotBot’ - Khan, Md. Raisuddin; Huq, NML; Billah, Md. Masum; Ahmmad, Syed Masrur (IOP Publishing, 2013)
To have a healthy, comfortable, and fresh civilized life we need to do some unhealthy households. Cleaning the dirty floor with a mop is one of the most disgusting and scary house hold jobs. Mopping robots are a solution of such problem. However, these robots are still on the way to be smart enough. Many points limit their efficiency, i.e. cleaning sticky dirt, having dry floor after cleaning, monitoring, cost etc. ‘HotBot’ is a mopping robot that can clean dirty floor with nice efficiency leaving no sticky dirt. Hot water can be used for heavy stains or normal water for usual situation and economy. It needs neither to be monitored during mopping nor to wipe the floor after it. ‘HotBot’ has sensors to detect obstacles and a control mechanism to avoid those. Moreover, it cleans sequentially and equipped with several accident-protection-systems. Moreover, it is also cost effective compared to the robots available so far.